Schizophrenia and violent crime: a population-based study. Issue 14 (26th March 2014) - Fleischman, A.; Werbeloff, N.; Yoffe, R.; Davidson, M.; Weiser, M.
Abstract : Background: Previous studies have found that patients with schizophrenia are more likely to be violent than the general population. The aim of this study was to investigate the association between schizophrenia and violent crime in the Israeli population. Method: Using the Israeli Psychiatric Hospitalization Case Registry we identified 3187 patients with a discharge diagnosis of schizophrenia. For each proband we identified parents and siblings, and gender- and age-matched controls for patients, parents and siblings. Information on violent crimes was obtained from police records. Results: Patients with schizophrenia were at increased risk for violent crimes compared with controls [odds ratio (OR) 4.3, 95% confidence interval (CI) 3.8–4.9], especially women (OR 9.9, 95% CI 6.2–15.7). Risk for violent crimes was higher among patients with co-morbid substance misuse than in patients without such co-morbidity (OR 5.1, 95% CI 4.2–6.3). Conclusions: The results of this study suggest that increased risk of violence is part of the clinical picture of schizophrenia and needs to be recognized as a legitimate, essential, aspect of clinical management.